Analisis Semiotika dalam Lirik Lagu Ala Bali- Perspektif Ferdinand de Saussure - Ahmad Amirul Kholid; Mas Tajuddin Ahmad (An-Nas, 2024)
Abstract:“This study analyzes the lyrics of "Ala Bali" using Ferdinand de Saussure's semiotic approach to uncover the layers of meaning related to unspoken love, longing, and waiting. Employing a descriptive-qualitative method, the research identifies linguistic signs (signifiers) in the lyrics, examines the relationship between signifiers and the signified, and interprets the literal, symbolic, and emotional meanings embedded within. The analysis reveals that the song's lyrics contain complex symbols reflecting emotional dilemmas, social norms, and the dynamics of love in Arab culture. Signifiers such as "حَبَّيْتُهْ بَيْنِيْ وَبَيْن نَفْسِيْ" and "عَلَى بَالِيْ" express the tension between personal feelings and societal constraints. The moral messages conveyed include the courage to express emotions and an awareness of longing as an integral part of the love experience. This study contributes to the field of semiotics by offering new insights into Arabic song lyrics and enriching the understanding of Arab cultural expressions through linguistic signs.”